Peixe-zebra como modelo animal para estudo de transtornos neuropsiquiátricos : manipulação farmacológica de receptores dopaminérgicos e avaliação do envolvimento do sistema purinérgico - Nabinger, Débora Dreher (2021)
Neuropsychiatric disorders are disabling diseases that affect a significant number of people. Although its biological basis is not fully understood, it is known that changes in neurotransmission systems play an important role in its pathogenesis. The dopaminergic and purinergic systems are involved in numerous brain functions, and are associated with many disorders. Pharmacological agents that interact with the neurotransmission systems allow investigating cellular and molecular responses mediated by them, which may elucidate the patophysiology of such disorders. Quinpirole, a dopamine D2/D3 receptor agonist, allows the study of mechanisms underlying neuropsychiatric disorders, using animal models. The zebrafish is widely used in translational biomedical research and has been successfully used in psychopharmacology studies. In the present study, three quinpirole administration protocols were performed in zebrafish and behavioral, morphological and biochemical analysis were performed. Quinpirole exposure (5.5, 16.7, 50 μM) during 1h in larvae (6 days post-fertilization, dpf) induced hyperactivity, anxiety-like behavior, erratic and repetitive movements, and impair optomotor responses. The effects observed were dependent upon feeding status, only fed animals showed behavioral alterations. Adult zebrafish (6 months) received two intraperitoneal injections of quinpirole with an inter-injection interval of 48h (0.5, 1.0, 2.0 mg/kg), and exhibited hypolocomotion, anxiety-like behavior, erratic and stereotypic movements, and memory impairment. The quinpirole treatment induced increased brain neurotrophic factor and glutamate levels, and decreased levels of serotonin. In the third protocol, exposure to quinpirole during 24h (5.5, 16.7, 50 μM) at 5 dpf led to late alterations. At 120 dpf, animals exposed to quinpirole exhibited anxiety-like behavior, erratic and stereotypic movements, and impaired memory. The enzymatic activity of ectonucleotidases, adenosine deaminase (ADA) and the ATP metabolism were evaluated. For larvae, quinpirole altered the nucleoside triphosphate diphosphohydrolase (NTPDase) activities by promoting a decrease in ADP hydrolysis, and induced increased ATP, AMP, ADO and INO levels. In adults, decrease in ADP hydrolysis and adenosine deamination was observed, indicating alterations on NTPDase and ADA activities. Additionally, increased ADP and decreased AMP, ADO and INO levels were observed. The analysis performed at 120 dpf after quinpirole exposure during development had no alterations on enzymatic activity. However, decreased levels for the nucleotide and nucleosides evaluated were observed. In summary, the behavioral alterations observed are part of the behavioral spectrum of several neuropsychiatric disorders. Furthermore, the results with larvae indicate that the behavioral effects of quinpirole exposure are depended upon feeding status – food intake, a naturally rewarding stimulus known to engage the dopaminergic system, became the receptors more susceptible to quinpirole’s effects. The protocol in adult zebrafish showed that more than behavioral alterations, quinpirole administration led to neuroplastic changes in the central nervous system of zebrafish. Furthermore, the third protocol showed that quinpirole exposure can lead to late behavioral alterations. Last, the findings of this study demonstrated that quinpirole administration may inhibit NTPDases and ADA activities, modulating nucleotide and nucleoside levels, indicating the involvement of purinergic signaling on neurological disorders. Thus, the present study shows that the use of quinpirole exposure may be an appropriate tool for the analysis of mechanics underlying neuropsychiatric disorders.